LOWER NILRADIKAL CONNECTED WITH ONE-SIDED IDEAL - Jusufi, Azir; Filipi, Kristaq (Matematichki Bilten, 2010)
Based on the ideas of Andrukievich and Rabjuhin for bonding the Jacobson radical of a right ideal [3], we intervened in the theory of lower Ber nilradikal, looking at him as connected with a one-sided ideal in an associative ring. In this paper we present some results obtained during this review, which brought us to the term lower nilradikal connected with one sided ideal.